1976
DOI: 10.1002/jcp.1040870209
|View full text |Cite
|
Sign up to set email alerts
|

Arrest of 3T3 cells in G1 phase in suspension culture

Abstract: 3T3 cells do not grow in Methocel suspension culture, while other permanent cell lines do. The viability of 3T3 cells in suspension remains unchanged for at least three days with respect to plating efficiency, vital staining and resumption of normal growth when transferred into monolayer culture. When monolayer 3T3 cells in G1 phase are suspended they remain in G1 phase. Cells already in S phase which are suspended complete ongoing DNA synthesis and mitosis and then are arrested in the G1 phase. Progress throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
0

Year Published

1978
1978
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(69 citation statements)
references
References 10 publications
3
66
0
Order By: Relevance
“…We previously showed that complementation with this isoform restored the susceptibility of Eker-Cdc6 cells to anchorage loss and destabilized CDC6 (29). Herein, we first confirmed that all of the effects of anchorage deprivation on G 1 (Fig. 3).…”
Section: Expression Of Tsc2 Isoform 4 Restores Susceptibility Of Ekersupporting
confidence: 68%
See 1 more Smart Citation
“…We previously showed that complementation with this isoform restored the susceptibility of Eker-Cdc6 cells to anchorage loss and destabilized CDC6 (29). Herein, we first confirmed that all of the effects of anchorage deprivation on G 1 (Fig. 3).…”
Section: Expression Of Tsc2 Isoform 4 Restores Susceptibility Of Ekersupporting
confidence: 68%
“…The requirement for anchorage is absolute and cannot be overridden by simple growth factor stimulation (1)(2)(3). Anchorage to the ECM is sensed by heterodimeric integrins in the plasma membrane, and a signal is transmitted to various downstream effectors (4,5).…”
mentioning
confidence: 99%
“…Otsuka and Moskowitz (1975) showed that 3T3 cells in S phase could be trypsinized and transferred to a methylcellulose suspension culture without affecting their ability to continue DNA synthesis. Although poorly quantitated, the authors also showed that at least some of these cells gave rise to mitotic figures.…”
Section: Discussionmentioning
confidence: 99%
“…Adhesion deprived NIH3T3 ®broblasts arrest in G1 phase (Otsuka and Moskowitz, 1975) due to down- regulation of many components of the cell cycle machinery , particularly cyclin A (Guadagno et al, 1993;Schulze et al, 1995). Furthermore, growth arrest by contact inhibition is associated with cyclin A down-regulation (Yoshizumi et al, 1995) while other cyclins, such as cyclin D1 continue to be expressed (Meyyappan et al, 1998;Yoshizumi et al, 1995).…”
Section: Rara-plzf Deregulates Cyclin a Expression In Vivomentioning
confidence: 99%